Analisis Pengaruh Faktor Marketing Mix Terhadap Keputusan Pembelian Minyak Goreng Kemasan Di Pasar Tradisional Sukaramai Medan - Alda Kartika; Tuty Ningsih (Institut Teknologi Sawit Indonesia, 2017)
Cooking oil is a main needs for Indonesia people. The customer chooses cooking oil based on their needs, there wants andpurchaseability. One alternative that can be usedby seller is by doing marketing mix analysis which coverproducts,price, location (distribution) and promotion in marketing strategy of cooking oil product in traditional marketing. The purpose ofthis research in general is to test and analyse the influence ofproduct on the purchase decision o f cooking oil, theinfluence ofpriceson the purchase decision o f cooking oil, theinfluence o f locationon the purchase decision o f cooking oil, the influence promotion on the purchase decision o f cookingoil in Sukaramai market in Medan.And simultaneously testing and analyzing the influence of marketing mix to purchase decision o f cooking oil in Sukaramai market in Medan. The research method used is multiple linier regression analysis and processed using SPSS 21. The research resultshowed that productvariable(Xl) partially had positive value with score T count<Ttable was 1,888<1,990 with the significantvalue o,209> a(0,05) means that didn't have significant influence to the customerpurchase decision (y)price variable (X2)partially hadpositive value with value t>t table was 3,168>1,950 with significant value 0,002 <a (0,00) means had significant Influence to customerpurchasedecision (y). Place variable (X3) partially hadpositive value with value T count >Ttable was 2,471 > 1,990 with significancy value 0,015< a (0,05) means had significant influence to the customer purchase decision (y) promotion variable (X4) partially hadpositive value with value T count < T table was 0,557 <1,990 and significant value 0,565 > a(0,05) means didn't have influence to the purchase decision (y). Product variable (XI), price(X2) place (X3) and promotion (X4) together had positive value with value Fcount > F table was 65,709 > 2,47 and significant value 0,000 < a (0,05) means had significant influence to the customerpurchase decision (y).